Ultrasound-guided Genicular Nerve Ablation with Alcohol Solution for Knee Osteoarthritis: A Case Series - Butarbutar, John; Phandu, Mirna; Lee, Kevin; Tasya, Earlene; Sulaeman, Wendell Sebastian (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Genicular nerve ablation using radiofrequency (RF) is a common minimally invasive procedure for painful osteoarthritic knees. However, the high cost and unavailability of equipment in many healthcare centers made this inconvenient for some patients. Some case reports tried the cheaper and newer method, using an alcohol solution to ablate the genicular nerves, showing considerable improvement in the patient's pain, functional knee score, and quality of life. We have attempted the ultrasound-guided genicular nerve ablation using alcohol solution in 6 patients with knee osteoarthritis to complement the body of evidence. We found that the genicular nerve ablation using alcohol solution is an excellent method for relieving symptoms of knee osteoarthritis if knee pain is the main symptom.